Indications, contraindications and clinical outcomes of the use of episiotomy: an integrative review - Gonzaga, Márcia Féldreman Nunes (2023)
To identify the indications, contraindications and clinical outcomes associated with the use of episiotomy. Integrative review. The inclusive criterion was complete studies, in Spanish, English and Portuguese, with publications between 2017 and 2021, seeking the latest on the subject in the literature. The exclusion criterion was scored as articles prior to 2017, duplicates, with a theme leak and with other languages, other than those chosen. Studies from the BDENF, LILACS, MEDLINE and PUBMED databases were selected. The search resulted in a total of 456 articles and, after applying the inclusive and exclusive criteria, after reading the title and abstract in pairs, 26 studies remained for full reading. Among them, some were characterized as duplicates and, performing their removal, a total of 12 articles were obtained, which composed this review. It is noteworthy that there are no direct indications for the use of episiotomy, observing only factors related to its use. Faced with this scenario, the routine use of episiotomy is contraindicated, that is, above the 10% recommended by the World Health Organization (WHO), since its practice can lead to numerous harmful clinical outcomes for the woman, in a short period of time and long term.